Design for test and qualification through activity-based modelling in product architecture design. (2nd November 2021) - Borgue, Olivia; Paissoni, Christopher; Panarotto, Massimo; Isaksson, Ola; Andreussi, Tommaso; Viola, Nicole
Abstract : Test and qualification (T&Q) phases take a significant portion of the time to market for critical products in the space industry, especially when introducing new technologies. Since T&Q are treated as standard procedures, they tend to be independent of the architectural design phases and kept away from design decisions. However, when introducing new technologies, qualification procedures may differ from those established in regular design scenarios, and the estimation of qualification costs and duration is problematic. There is a lack of design for qualification methods capable of modelling these activities in early phases and use those models to support the architecture design of products with affordable test and qualification phases. In this article, a computer-assisted, model-based design method to model T&Q activities concerning early product architecture designs is proposed. Product architecture alternatives, test schedules and cost are connected through the quantification of T&Q drivers and driver rates. The design method is demonstrated using a case study about electric propulsion for satellites. The method is applicable for design situations where the choice of technology has a strong dependence on the qualification procedure.